Heroism As Portrayed in Henry Gilbert’s Novel Robin Hooda and Rizki Ridyasmara’s Novel Pitung: A Comparative Literature Analysis - Refieta, Dita (Jurnal Pendidikan Indonesia, 2021)
This thesis contains a study of comparative literature which involves two novels of different nations with similar motifs; heroism. The purpose of this study is to find out how heroism in the two novels and find the similarities and differences regarding the thirteen central features of the hero possessed by the leading character. The leading characters, Robin Hood and Pitung are the heroes who concern for other people in need, through their actions by stealing from the rich to give to the poor. The study also involves looking at the intrinsic elements to look at the similarities and differences found in the two novels. In completing the analysis, the writer uses the descriptive qualitative method which represents all the data in the forms of words and sentences. The writer collects data from various sources, including the novels Robin Hood by Henry Gilbert, Pitung by Rizki Ridyasmara, relevant books, articles, and journals to support the analysis. Based on the analysis it concluded that the novels show similarities and differences regarding the central features of the hero that is possessed by the two leading characters of both literary works. Robin Hood shows braver as physically act while Pitung shows more courage as mentally active.